Penggunaan Hak Angket Oleh DPR RI Dalam Mengawasi Kebijakan Pemerintah - Subardjo, Subardjo (Faculty of Law, Universitas Ahmad Dahlan, 2016)
Inquiry rights is the right of Parliament to conduct an investigation on the implemen-tation of a law or government policies relating to the important things, strategically, and im-pacted peoples lives, nation, and state that allegedly contrary to the legislation. The rights, in its use is different between Law No. 6 of 1954 and Law No. 27 of 2009, both the implementation and the effectiveness in controlling government policy.This paper used sociological juridical approach by outlining the legislation related to inquiry rights and analyzing sociological aspect of the use of the inquiry rights by the members of Republic Indonesia Parliament.In conclusion, the inquiry rights ofÂ Parliament members has been used normatively and tend to be political, they just want to be safe by sheltering under the government power to get something or sheltering on behalf of the people to draw sympathy, so that in the next election they could boost the votes.